A Model of Inclusive Digital Public Financial Governance to Support Green Economic Transformation in Archipelagic Regions - Wilda Fatmala; Murni Sari; Filasti Rahma; Sholeha Tera Aprilia (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The transformation toward a green economy represents a strategic agenda for achieving sustainable development, particularly in archipelagic regions such as Baubau City, which faces fiscal constraints and geographical challenges. This study examines the influence of inclusive public financial governance and digitalization of public finance on green economic transformation, with the effectiveness of public financial management serving as a mediating variable. The research applied a mixed-methods approach, involving 126 quantitative respondents determined using the Slovin formula and ten qualitative informants selected purposively. Quantitative data were analyzed through multiple regression and the Sobel test, while qualitative data were collected through interviews and focus group discussions to enrich the empirical context. The findings reveal that inclusive public financial governance significantly affects the effectiveness of public financial management but does not directly influence green economic transformation. In contrast, digitalization of public finance has a significant impact on both financial management effectiveness and green economic transformation. The effectiveness of public financial management also contributes significantly to green economic transformation but does not serve as a significant mediating variable. Overall, the study concludes that digitalization of public finance is a key driver in accelerating green economic transformation in archipelagic regions. Meanwhile, inclusive governance should be strategically aligned with green fiscal policies to ensure tangible contributions to sustainable and environmentally responsible development.